Catechols from abietic acid - Gigante, B (2015)
Catechols from abietic acid were prepared by a short and good yielding chemical process and further evaluated for several biological activities namely, antifungal, antitumoral, antimutagenic, antiviral, antiproliferative and inhibition of nitric oxide. Their properties were compared with those of carnosic acid (6), a naturally occurring catechol with an abietane skeleton and known to possess potent antioxidant activity, as well as anticancer and antiviral properties. From all the synthetic catechols tested compound 2 showed the best activities, stronger than carnosic acid. (C) 2003 Elsevier Science Ltd. All rights reserved.